Provocation and Localization of Arrhythmogenic Triggers from Persistent Left Superior Vena Cava in Patients with Atrial Fibrillation - Minami, Kentaro; Nakamura, Kohki; Maeno, Eiko; Iida, Keitaro; Saito, Ikuta; Masuyama, Taiki; Kitagawa, Yoshiyuki; Nakajima, Toshiaki; Nakatani, Yosuke; Naito, Shigeto; Toyoda, Shigeru; Chovanec, Milan; et al. (Journal of clinical medicine, 2023)
BACKGROUND: Although pulmonary vein isolation (PVI) is an established procedure for atrial fibrillation (AF), non-PV foci play a crucial role in AF recurrence. Persistent left superior vena cava (PLSVC) has been reported as critical non-PV foci. However, the effectiveness of provocation of AF triggers from PLSVC remains unclear. This study was designed to validate the usefulness of provoking AF triggers from PLSVC. METHODS: This multicenter retrospective study included 37 patients with AF and PLSVC. To provoke triggers, AF was cardioverted, and re-initiation of AF was monitored under high-dose isoproterenol infusion. The patients were divided into two groups: those whose PLSVC had arrhythmogenic triggers initiating AF (Group A) and those whose PLSVC did not have triggers (Group B). Group A underwent isolation of PLSVC after PVI. Group B received PVI only. RESULTS: Group A had 14 patients, whereas Group B had 23 patients. After a 3-year follow-up, no difference in the success rate for maintaining sinus rhythm was observed between the two groups. Group A was significantly younger and had lower CHADS2-VASc scores than Group B. CONCLUSIONS: The provocation of arrhythmogenic triggers from PLSVC was effective for the ablation strategy. PLSVC electrical isolation would not be necessary if arrhythmogenic triggers are not provoked.